MANAJEMEN PEMBELAJARAN IPA SISWA SD MELALUI PENERAPAN METODE INKUIRI - Dalimin Dalimin Dalimin (Manajer Pendididikan, 2016)
In this study, the problem is the result of learning science very low, therefore researcher is working to overcome these problems with the learning management by inquiry in.Research conducted as a Class Action Research The subject of this studyis the sixth grade students of SD Negeri 02 Kepahiang. The research instruments used were observation sheet and test sheet. The results obtained in this study in the first cycle average value of 69.90 with a presentation evaluating student mastery learning 50.75%. In the second cycle obtained average value evaluation of student mastery learning 77.80 with the percentage increasing to 70.85%. The third cycleobtained average value of student evaluation 85.60. with learning completeness percentage increased to 80.85%. It can be concluded that the learning management by inquiry can improve learning outcomes and student activity in learning science.Keywords: management, inquiry, learning, science.